Socioeconomic Structures in the Arab Gulf States and Democracy - Azam, Muhammad (Annals of Human and Social Sciences, 2024)
The objective of this study is to examine the media, economic, and education sectors, while also assessing the state of civil society and human rights in the Gulf region during the first decade of the twenty-first century. In the wake of September 11, 2001 events, the ruling Arab dynasties of the Gulf faced significant pressure from the American government to liberalize their political, social, and economic frameworks. This research study is grounded in both primary and secondary source materials. The challenge faced by the Gulf region is not one of low literacy rates, but rather pertains to the quality and nature of the education. The economic status of the Gulf states may be characterized as economic monarchism. The most alarming conditions are evident in the realm of human rights.Reforms to raise the standard of education in the region are needed in order to uphold democratic ideals